MENINGKATKAN PEMAHAMAN SISTEM PENGKONDISIAN UDARA PADA MOBIL BAGI GURU, LABORAN DAN SISWA BIDANG OTOMOTIF - Rines Rines; Wibowo Kusbandono; PK Purwadi (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2018)
There existed several problems that occur in several vocational schools related to the results of the implementation of the learning. In some vocational schools majoring in automotive, it was found that: (a) understanding and mastering the material of the car air conditioning system in students was still incomplete and not yet in-depth. (b) students still had difficulty understanding the air conditioning system on the car (c) there is no solution yet to make it easier for students to understand the car's air conditioning system in a complete and in-depth manner. The purpose of this service is to help overcome these problems. The training is intended for teachers, laboratory assistants and vocational students in the automotive department. The methods used were: training, demo, question and answer and joint discussion. The result of this service was an increase in the competence of teachers, laboratory staff and students. Teachers and laboratory assistants: (a) have a more complete and in-depth understanding of air conditioning systems (b) have the ability to design, make/assemble and produce props for air conditioning systems in cars (c) have the ability to develop/innovate in assembling conditioning systems air on the car. Students: (a) get a more complete and in-depth understanding of the material of the air conditioning system in the car (b) it is easier to get an understanding of the air conditioning system material in the car on the car by using the air conditioning system display equipment in the car. Other results of this service were (a) obtaining appropriate technology in the form of visual aids for car conditioning systems and (b) learning methods that facilitate understanding of air conditioning systems in cars.